A review on propagation of secure data, prevention of attacks and routing in mobile ad-hoc networks. (8th November 2019) - Borkar, Gautam M.; Mahajan, A.R.
Wireless communication formly mobile ad-hoc network (MANET) plays a significant role in modern technology for transmitting the packets from source node to destination node. The absence of any central contrivance makes MANETs more prone to cyber-attacks. So it is expected to meet the different security requirements such as authentication, confidentiality, integrity, anonymity, and availability. So this paper, developed a detailed survey about the techniques used for solving the various issues like security, authentication and routing. In addition to that, the authentication problem is also focused by providing more security by means of identifying one another. Moreover, the problem of incorporating security into routing protocols, many algorithms have been employed which is very challenging to find out the optimal and efficient method that can be used globally. Finally paper analysed various existing techniques and then critically analysed the work done in the field of MANETs.